Measurement method best correlates with body mass index: WHR, PBF and VF. / Noor Fatihah Ilias, Nurul Najwa Aminul Mahzan and Muhammad Danial Noor Hamidi - Ilias, Noor Fatihah; Aminul Mahzan, Nurul Najwa; Noor Hamidi, Muhammad Danial (Universiti Teknologi MARA, 2020)
The body mass index (BMI) had been the most measured to characterize body composition in an individuals. However, BMI has been criticized as being an inaccurate measured of body fatness among active individuals. Therefore, the aim of this study was to identify the relationship between BMI and waist to hip ratio (WHR), percentage body fat (PBF) and visceral fat (VF) among active individuals. The design used in this study was descriptive correlation design. Subjects (n = 242) were students from Faculty of Sports Science and Recreation, UiTM Shah Alam. BMI, WHR, PBF and VF measurements was using Bio Impedance Analysis (BIA). There was a positive relationship between BMI and WHR, PBF and VF. Results showed high relationship between BMI and WHR (r = 0.615, p = 0.000). Whereas, moderate relationship between BMI and PBF (r = 0.421, p = 0.000). Besides, there was high relationship between BMI and VF (r = 0.529, p = 0.000). Based on results, BMI was moderate to high relationship between WHR, PBF and VF. Therefore, BMI can be considered accurate and appropriate measurement to determine body fatness among active individuals.